THU0202 Prospective evaluation of aortic structural damage (aneurysm/dilatation) using a predefined screening protocol in biopsy-proven giant-cell arteritis patients during long-term follow-up. (23rd January 2014) - García-Martínez, A.; Arguis, P.; Prieto-González, S.; Hernández-Rodríguez, J.; Espígol, G.; Corbera, M.; Alba, M.; Tavera, I.; Planas, E.; Cid, M.C.
Abstract : Background: In a previous study of 54 patients with biopsy-proven giant-cell arteritis (GCA) we found that 22.2% (12 patients) had significant aortic structural damage (ASD) (aneurysm/dilatation) after a median follow-up of 5.4 years. Development of ASD was not related to persistence of clinically apparent disease or elevation of acute-phase reactants or pro-inflammatory cytokines during follow-up (1) The outcome of ASD after longer follow-up has never been prospectively evaluated. Objectives: To assess the development of new ASD and the outcome of previously detected abnormalities after longer follow-up. Methods: Patients from the initial cohort who continued their follow-up visits in our department were subjected to the same screening protocol every four years approximately. The screening protocol consisted of a chest X-ray and a CT scan if aortic aneurysm was suspected or changes respect to the baseline X-ray were observed. The abdominal aorta was evaluated by ultrasonography (US). ASD was defined when the ascending aorta measured >4 cm in diameter, the aortic arch or the descending aorta ≥4cm, the abdominal aorta >3 cm or, when the aorta exhibited a fusiform dilatation. Results were compared to those obtained from the previous screening. Results: Eighteen of the 54 patients from the original cohort had died or were lost tofollow-up before they could be re-evaluated. The remaining 36 patients were subjected to a new screening (median follow-up at the time of second screening 8.5 years, range 8-12). In 7 of these patients ASD had been detected in the previous evalutation (1 involving the abdominal aorta and 6 the thoracic aorta). In the second screening the abdominal aneurysm remained stable whereas thoracic ASD increased in diameter. Three patients had newly discovered thoracic ASD not detected in the first screening. One of them died of an aortic dissection 9 years after the diagnosis of GCA. The remaining 26 patients did not show changes in the chest X-ray when compared to the baseline X-ray, or, if changes were suspected, the CT scan did not evidence significant aortic abnormalities. No new abdominal aneurysms were observed by US. To date, 7patients have been subjected to a third screening after a follow-up of 13 years (range 11.6-15), with no evidence of new ASD in any of them. Overall, 27.7% of patients from the original cohort developed ASD after a median follow-up of 10 years (range 4.3-15). Conclusions: Our study suggests that GCA-patients develop ASD mainly but not exclusively, within the first 5 years of follow-up. Once ASD occurs, dilatation increases over time, particularly in the thoracic aorta underlining the need for periodic evaluation. These results should be confirmed in a larger series of patients. References: Ana García-Martínez, José Hernández-Rodríguez, Pedro Arguis, Pilar Paredes, Marta Segarra, Ester Lozano, et al. Development of aortic aneurysm/dilatation during the followup of patients with giant-cell arteritis: a cross-sectional screening of fifty-four prospectively followed patients. Arthitis Rheum (AC&R) 2008;59:422-430. Disclosure of Interest: None Declared